Oversight of Dual-Use Research: What Role for Ethics Committees? - Magdalena Guraiib, Maria; Ross, Anna Laura; Frewer, Andreas; Sprumont, Dominique; Gooshki, Ehsan Shamsi; Dzenowagis, Joan; Alois Reis, Andreas (Health Security, 2024)
The World Health Organization (WHO) Global Guidance Framework for the Responsible Use of the Life Sciences addresses the governance of biorisks, including dual-use research, for countries. It emphasizes engaging multisectoral stakeholders such as governments, scientific bodies, health and research institutes, standard-setting organizations, funding bodies, and others. Ethics constitutes a key component of the framework. Given the high social impact of such research and the importance of trust, risk, and benefit, national ethics committees could make a valuable contribution by providing ethical guidance in the decisionmaking process. The purpose of this study was to examine the role of national ethics committees in the context of governance and oversight of dual-use research at the national level. We conducted a landscape analysis of the activities of ethics committees in dual-use research oversight. We also searched the WHO database on National Ethics Committees for publications related to dual-use research and/or misuse of life sciences research and gathered additional documentation from national ethics committees websites and through author contacts. Results showed that in the context of the wide range of oversight mechanisms for dual-use research in countries, national ethics committees have contributed to guiding policy and assessing dual-use research risks in only a limited number of countries. Recommendations from those countries include establishing a multistakeholder, coordinated oversight mechanism at the country level; strengthening international linkages to guide, harmonize, and reinforce national and international efforts; and involving ethics committees as an expert resource in the governance and oversight process.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Biosecurity/biosafety; Dual-use research; Ethics; Ethics committees; Health policy; National ethics committees